Conversion of trans‐Diboran(4)yl Platinum Complexes into Their cis‐Bisboryl Analogues. Issue 43 (11th September 2013) - Braunschweig, Holger; Damme, Alexander; Kupfer, Thomas
Abstract The diboran(4)yl trans‐[(iPr3P)2Pt(Br){B(NMe2)B(NMe2)Br}] (1) is readily converted into its cis‐bisboryl analogues 2 and 3 by reaction with the chelating bisphosphines 1, 2‐bis(dicyclohexylphosphino)ethane (dcpe) and 1, 1‐bis(dicyclohexylphosphino)methane (dcpm), respectively. A plausible mechanism of this transformation consists of a sequence of reductive diborane(4) elimination and subsequent reoxidative addition of its BB bond to the low‐valent platinum centers. Thus, the forced cis configuration of the phosphine ligands induces a change in the preferred reaction site of the diborane(4) with respect to oxidative addition. The reactions proceed with high selectivities, and the cis‐bisboryl complexes 2 and 3 were isolated in moderate yields (55 and 46 %). Moreover, their identity was clearly verified by NMR spectroscopy and X‐ray diffraction studies.